Analysis Of The Influence Of Financial Literacy And Financial Technology On Financial Satisfaction With Financial Management Behavior As Medition - Ameera, Najwa Saffa; Yuniningsih, Yuniningsih (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
inancial satisfaction is one of the goals that individuals want to achieve to obtain well-being in life, as a result of decisions in financial behavior. This is influenced by individual behavior in managing finances, which is also shaped by an individual's financial literacy and their use of financial technology. This research aims to investigate the influence of financial literacy and financial technology on financial satisfaction, with financial behavior acting as an intervening variable, in Management students of UPN "Veteran" East Java. This research adopts a quantitative approach, utilizing primary data obtained through a questionnaire. The research sample consisted of 95 active students of the Management study program at the Veteran National Development University of East Java who were selected using non-provbability sampling with a purposive sampling technique based on certain criteria. The data were analyzed using Structural Equation Movdeling (SEM) with the help of SmartPLS software. Data acquisition was obtained from a survey method questionnaire through the distribution of questionnaires, which contained several statements related to the research. The data in this study were analyzed using the Partial Least Squares (PLS) method with thev assistance of SmartPLS sovftware. The findings indicate that both financial literacy and financial technology positively influence financial satisfaction. Moreover, financial management behavior effectively mediates the relationship between financial literacy, financial technology, and financial satisfaction